2018
DOI: 10.1016/j.jaci.2018.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Accidental food allergy reactions: Products and undeclared ingredients

Abstract: A wide range of food products are causing accidental reactions in patients with food allergy. Eight different allergens not declared on the ingredient lists were detected in the culprit food products, all of which were representative of allergens regulated in the European Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 31 publications
(52 reference statements)
3
65
1
3
Order By: Relevance
“…5,24 Patients had to fill in a questionnaire after every accidental allergic reactions to food over a 1-year period. This study was part of a study concerning accidental allergic reactions to food in adults.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…5,24 Patients had to fill in a questionnaire after every accidental allergic reactions to food over a 1-year period. This study was part of a study concerning accidental allergic reactions to food in adults.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…[1][2][3][4][5] Avoidance of the trigger food(s) is central to management by patients but accidental ingestion is common, causing frequent and sometimes life-threatening reactions. [6][7][8][9][10] Admission rates for anaphylaxis have increased approximately threefold between 2005 and 2012 in several countries. [11][12][13] Management of both food allergy (by patients and health practitioners) and allergens (by industry) is currently hindered by gaps in the evidence and in the implementation of our current knowledge compounded by a lack of consensus.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A systematic review and meta‐analysis has reported the pooled lifetime prevalence of self‐reported FA as 17.3% (95% CI: 17.0‐17.6) . Avoidance of the trigger food(s) is central to effective self‐management but unintentional consumption is common causing frequent reactions, some of which may be life‐threatening . Admission rates for anaphylaxis have increased approximately threefold between 2005 and 2012 .…”
Section: Introductionmentioning
confidence: 99%